Working Fluid Selection and Optimal Power-to-Weight Ratio for ORC in Long-Haul Trucks. (September 2017) - Pili, Roberto; Castro Pastrana, Jesus D.; Romagnoli, Alessandro; Spliethoff, Hartmut; Wieland, Christoph
Abstract: In 2013, about 82% of the total CO2 emissions from transportation systems in the U.S. were caused by road transportation, highly based on internal combustion engines (ICE). Organic Rankine Cycles (ORC) are a waste heat recovery (WHR) technology that can contribute significantly to reduce environmental impact of road transportation. A trade-off has to be found between the improved fuel energy utilization and the weight and volume of the ORC, which increase the vehicle load and reduce the available space for transportation. In the present work, 17 working fluids are analyzed as possible candidates for WHR with direct-evaporation ORC in long-haul trucks. The preheater/evaporator is modelled as a finned shell-and-tube heat exchanger, while the condenser is an air-cooled finned flat-tube heat exchanger, as in common truck radiators. The ORC process is optimized for each fluid in terms of maximum power output, taking into account the impact of the working fluid on the heat exchanger weight and volume. The heat exchangers are modelled in MATLAB®. The results show that acetone and ethanol can recover more than 6 kW of mechanical power, but the system would present large weight and required space. Isobutane shows the highest power-to-weight and power-to-volume ratio (234 W/kg and 277 W/dm 3 resp.), but the net power output is lower. Cyclopentane and pentane allow a good trade-off between power output and space requirement. The discussed procedure can be also applied to other transportation systems, where the condenser might have to be adapted to different boundary conditions.